2014
DOI: 10.1353/jmm.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

Beauty Ideals in the Checkout Aisle: Health-Related Messages in Women’s Fashion and Fitness Magazines

Abstract: This study analyzed magazine covers, as well as editorial and advertising content in women's health/fitness and beauty/fashion magazines. Results indicated that models in these magazines were of relatively the same thinness, and that there was very little emphasis placed on weight loss for the sake of overall health. Models in fashion/beauty magazines were glamorous, while models in health/fitness magazines were conspicuously thin. Health and body image content was generally framed as appearance-related rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This was one of the first studies to investigate the effects of health vs. appearance framing in different contexts. This is important because these strategies are widely used in social media (3,6) as well as in magazines (5,17). However, emphasizing the goal of improving the appearance of an individual rather than contributing to the individual's health can lead to certain negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was one of the first studies to investigate the effects of health vs. appearance framing in different contexts. This is important because these strategies are widely used in social media (3,6) as well as in magazines (5,17). However, emphasizing the goal of improving the appearance of an individual rather than contributing to the individual's health can lead to certain negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies in the research area of health communication often distinguish between two media frames: appearance frames and health frames. As content analyses showed (4,5,16,17), appearance frames emphasize the importance of healthy eating and doing sports to look good (i.e., sexy, attractive), whereas health frames focus on the health aspects connected with such behaviors (i.e., healthy, feeling good). Overall, content analyses revealed that, in health and beauty magazines (4,5,16,17), as well as on social media (3,6,(18)(19)(20), health behaviors are oftentimes promoted in connection with appearance aspects.…”
Section: Framing Effects In Connection With Health Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional paper published in the Journal of Magazine & New Media Research examined body-related content in beauty/fashion magazines vs. women's health/fitness magazines, two genres conceptualized by the researchers. 20 Conlin and Bissell's ambitious study 21 quantified coverline content, models' body sizes in photographs, and framing of health messages in articles and ads. The authors found that both genres used thin models to emphasize appearance and glamour over fitness and health.…”
Section: Magazine Health Contentmentioning
confidence: 99%